Facile synthesis of reversibly crosslinked poly(ionic liquid)-type gels: Recyclable supports for organocatalysis by N-heterocyclic carbenes. (October 2018) - Garmendia, Sofiem; Lambert, Romain; Wirotius, Anne-Laure; Vignolle, Joan; Dove, Andrew P.; O'Reilly, Rachel K.; Taton, Daniel
Graphical abstract: Highlights: A metal-free ion-exchange strategy is implemented to achieve physically crosslinked imidazolium-based copoly(ionic liquid)s. The gel-type structure serves as heterogeneous thermally latent polymer-supported N -heterocyclic carbenes (NHCs). Organocatalyzed molecular reactions can be performed in presence of the physically crosslinked gel-supported NHCs. The crosslinked gel can be recycled and reused without any loss of efficiency after 5 catalytic cycles. This work introduces an innovative alternative for supporting NHCs toward their facile manipulation for organocatalysis. Abstract: Owing to their broad modularity, polymeric versions of ionic liquids, referred to as poly(ionic liquids) (PILs), have attracted increasing attention as recyclable polymer-supported (pre)catalysts for various chemical transformations. Herein, an imidazolium-based statistical copolymer based on PIL (=coPIL) is specifically designed by free-radical copolymerization of styrene and 4-vinylbenzylethyl(benz)imidazolium chloride. A selective ion-exchange reaction can be subsequently achieved to incorporate bio-sourced difunctional sebacate-type counter-anions, causing the physical crosslinking of the coPIL precursor via electrostatic interactions between pendant imidazolium moieties and sebacate dianions. The as-obtained gel-type precursor exhibits a thermally latent behavior in THF, proving advantageous for a facile manipulation and practical use for organocatalysis. Upon heating, typically at 80 °C, interaction between the sebacate dianion and the proton in C2-position of the imidazolium moieties generates polymer-supported N -heterocyclic carbene units that act as catalytic active species towards NHC-organocatalyzed reactions, namely, benzoin condensation, transesterification and cyanosilylation. The PIL-based gel precursors can be restored, recycled and reused by simply cooling down, i.e. with no need of an external chemical reagent, due to the shift of the intramolecular equilibrium towards the formation of imidazolium sebacate-type units. Overall, this novel gel-type copolymeric platform shows a thermo-responsive behaviour, and proves particularly versatile for heterogeneous organocatalysis.